2010
DOI: 10.1111/j.1439-0426.2010.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of wild and farmed Tor putitora from Pakistan

Abstract: Length-weight relationships (W = a TL b ) were estimated for wild and farmed Tor putitora obtained from River Korang, Islamabad and Attock District, Pakistan, respectively. The results indicate, W = 0.0171 TL 2.85 for wild and W = 0.1000 TL 2.33 for farmed. Total length ranged from 18.0 to 40.2 cm for male and 31.6 to 37.0 cm for female wild Tor putitora, indicating that the fish are now much smaller. The first reference of length-weight relationships for Tor putitora is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
5
2
Order By: Relevance
“…The estimates of parameter b of LWR ranged from 2.99 to 3.21 in the present study. These values are quite different from the other closely related species of this genus, Tor putitora , b = 2.85 (allometric growth) from the River Korang, Islamabad, Pakistan (Naeem et al., 2011). This may be the result of slightly different size ranges of the studied samples, perhaps affected as well by differences in the sample size, sampling and preserving methods.…”
Section: Discussioncontrasting
confidence: 64%
“…The estimates of parameter b of LWR ranged from 2.99 to 3.21 in the present study. These values are quite different from the other closely related species of this genus, Tor putitora , b = 2.85 (allometric growth) from the River Korang, Islamabad, Pakistan (Naeem et al., 2011). This may be the result of slightly different size ranges of the studied samples, perhaps affected as well by differences in the sample size, sampling and preserving methods.…”
Section: Discussioncontrasting
confidence: 64%
“…The Kenyan IUCN red list threatened fishes biometric information has been quite insufficient despite a number of studies having been conducted within the Asian countries (Hossain et al, 2012;Gupta et al, 2011;Muchlisin et al, 2010;Naeem et al, 2010Naeem et al, , 2011Patiyal et al, 2010;Sani et al, 2010;Sarkar et al, 2009;Yousaf et al, 2009). In this study, the 10 species size structures demonstrated some marked length size class range differences (Table 1).…”
Section: Discussionmentioning
confidence: 79%
“…Mahseer are pelagic fish which swim actively due to their habitat in fast flowing foothills streams with highwater quality (Dinesh et al, 2010;Ambili et al, 2014;Raghavan et al, 2017). Actively swimming fish which live in fast flowing water usually have a value of b < 3 because more energy is allocated for swimming than for growth in terms of weight gain (Shukor et al, 2008;Muchlisin et al, 2010;. The same phenomenon was observed in the mahseer populations at both study sites.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 71%